2014
DOI: 10.1002/cm.21197
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule orientation and spacing within bundles is critical for long‐range kinesin‐1 motility

Abstract: Cells rely on active transport to quickly organize cellular cargo. How cells regulate transport is not fully understood. One proposed mechanism is that motor activity could be altered through the architecture of the cytoskeleton. This mechanism is supported by the fact that the cytoskeletal network is tightly regulated in cells and filament polarity within networks dictates motor directionality. For instance, axons contain bundles of parallel microtubules and all cargos with the same motor species will move in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
27
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 44 publications
7
27
1
Order By: Relevance
“…In agreement with previous research, we first show that axonal projections have a higher GTP-tubulin density as compared to dendrites 21 This could be linked to the fact that kinesin motors bound to cargo have more difficulty traversing obstacles owing to their limited step-size and short neck-linker as compared to dynein motors [51][52][53][54] . Increasing the amount of stable, elongated tubulin dimers in neurons also led to increased anterograde-but without affecting retrograde velocities.…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with previous research, we first show that axonal projections have a higher GTP-tubulin density as compared to dendrites 21 This could be linked to the fact that kinesin motors bound to cargo have more difficulty traversing obstacles owing to their limited step-size and short neck-linker as compared to dynein motors [51][52][53][54] . Increasing the amount of stable, elongated tubulin dimers in neurons also led to increased anterograde-but without affecting retrograde velocities.…”
Section: Discussionsupporting
confidence: 91%
“…4C). Prior work has shown that kinesin-1 motors have difficulty navigating obstacles such as microtubule-associated proteins and other roadblocks164344.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro, microtubule bundles obtained via excluded-volume interactions under macromolecular crowding conditions are tightly packed with wall-to-wall contacts, in contrast with the regularly spaced microtubules observed in tau-mediated bundles [30]. Microtubule-based transport should most probably be impaired in such compacted structures [45], which would be detrimental for most axonal functions.…”
Section: Resultsmentioning
confidence: 99%